Mathematical Modeling of Genistein's Inhibitory Effects on the Tryptophan Pathway: Enzyme Blockage and NAD Dynamics - Bhattacharjee, Sudipa; Bhadra, Preetha (2024 2nd International Conference on Signal Processing, Communication, Power and Embedded System (SCOPES), 2024)
The kynurenine pathway (KP) is a crucial route for tryptophan metabolism, leading to NAD+ production and having a significant role in neurodegenerative disorders. This work examines the effects of genistein, a bioactive isoflavone from soybeans, on the KP using a mathematical model. It focuses on the inhibitory effects of genistein on enzymes like tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO). Our simulation results show that while downstream metabolites such as N-formylkynurenine (NFK), quinolinic acid (Qa), and 3-hydroxykynurenine (HK) decrease, genistein enhances the steady-state concentration of tryptophan (TRP) and NAD+. This implies a mechanism of competitive inhibition, specifically on IDO, leading to a build-up of TRP and a decrease in NAD+ precursors. Further evidence supporting the impact of enzyme inhibition on metabolic fluxes came from flux balance analysis (FBA). These results demonstrate the potential of genistein to modulate the kynurenine pathway, which may have consequences for treatment approaches aimed at neurodegenerative and inflammatory disorders.